2003
DOI: 10.1034/j.1600-051x.2003.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization during de novo plaque formation

Abstract: In the present investigation, the preparatory phase established a situation with minimal gingival inflammation and close to zero amounts of dental plaque. The Day 0 plaque samples exhibited high proportions of Actinomyces species. During the 4 days of no oral hygiene, there was a small increase in total numbers of organisms as well as a modest increase in the proportion of "disease-associated" taxa such as species of the "orange complex" species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 41 publications
(43 reference statements)
9
41
0
4
Order By: Relevance
“…Early colonization of tooth-associated ecosystems is a specific and selective process, and the development of a mature community is influenced by these early interbacterial as well as host-bacterium interactions (28,33,42). In the gastrointestinal tract, it has been shown that early colonizers occupy this spatial niche in large numbers, thereby playing an important role in resisting colonization by pathogenic species.…”
mentioning
confidence: 99%
“…Early colonization of tooth-associated ecosystems is a specific and selective process, and the development of a mature community is influenced by these early interbacterial as well as host-bacterium interactions (28,33,42). In the gastrointestinal tract, it has been shown that early colonizers occupy this spatial niche in large numbers, thereby playing an important role in resisting colonization by pathogenic species.…”
mentioning
confidence: 99%
“…Additionally, after 4 days of biofilm growth, a visible dental biofilm layer forms. High percentages of visible supragingival biofilms have been observed clinically within this time frame 25 . Therefore, the four day growth period was chosen to simulate a real clinical situation widely confirmed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Çocuklarda dişler sürdükten hemen sonra oral hijyen sağlanmaz ve düzenli fırçalama alışkanlığı kazandırılmazsa, bakteriyel biyofilm tabakası oral çevreyle ilişkili olan diş yüzeyine ve gingival marjinlere yerleşerek gingival inflamasyonu başlatabilir (6). Kanıtlar, subgingival plak içindeki gramnegatif bakterilerin ve anaerobların sayısının artmasıyla periodontal hastalıkların geliştiğini göstermektedir (7). Periodontal hastalıklarla sıkça ilişkilendirilen mikroorganizmalar; Aggregatibacter (Actinobacillus), Porphyromonas gingivalis, Tanerella forsythensis ve Treponema denticola' dır (8).…”
Section: Peri̇odontal Hastaliklarda Eti̇yoloji̇unclassified